The power of controversy: the effect of a standard controversy in consumer intentions - Alves, Bernardo Gomes (2021)
This work studies the impact of brand controversies on consumer perception, while analyzing if people with low levels of control may be more susceptiblet o be attracted by those brands, even when they do not have an opinion on the controversial topic. An experiment was undertaken in which participants answered several questions regarding their perception of brands and what their intentions would be in a similar situation. Results demonstrated that companies involved in controversies signal power and control, even for consumers that do not support any side in the controversy. Manifesting interest in the topic showed to meditate that effect, indicating the existence of an activating variable.